Sistem Persediaan Obat Menggunakan Metode Moving Average Dan Fixed Time Period With Safety Stock - Nurkholis, Andi; Oktora, Putri Suci (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The Rahman Pharmacy business process is currently still running manually, namely recording the name, number, and price of the medicine purchased from the supplier into a piece of paper and then calculating using a calculator based on the purchase. In the business process, there are still errors when recapitulating daily transactions caused by paper notes is lost. So far, Apotek Rahman often runs out of merchandise, which can disappoint buyers. Another problem faced by Apotek Rahman is that medicine can accumulate. It can be detrimental because they have not implemented an inventory control system. This study aims to develop a website-based inventory information system to help Rahman Pharmacy manage computerized medicine data so that the work of managing incoming medicine, outgoing medicine, and the process of updating stock items becomes more effective. To produce medicine inventory recommendations, the moving average and fixed time period with safety stock methods are used. Each interested user can easily access every report on the purchase and sale of medicine. The system will provide updated stock information to consider when ordering medicines. In addition, the system can also provide recommendations for the procurement process so that it can be known when to order medicine based on the safety stock method, how many items are ordered, and provide the cost of inventory every time an item is purchased.